Per Connection Classifier Load Balancing dan Failover MikroTik pada Dua Line Internet - Taufik Rahman; Eko Sulistianto; Aji Sudibyo; Sumarna Sumarna; Bambang Wijonarko (Jurnal Informatika, 2021)
Internet is a primary need for all people. Many companies integrate Web sites with back-office systems such as databases. Problem that occurs is that the utilization of the two internet lines is less than optimal and efficient. This happens because the two lines are not in the same network. Likewise at PT. ICC Export, it can be seen from two internet lines that are not managed and go directly to switch. so that there is often a buildup of internet traffic on one line, resulting in slow internet access. When one internet line is disconnected, internet connection will automatically be disconnected because modem is not managed by router, so it can't back up automatically. Purpose of making load balancing and failover at PT. ICC Export to try a solution if one of two internet lines is dead, other line is active and if both lines are active then it can run simultaneously. Per Connection Classifier Load Balancing and Failover MikroTik on Two Internet Lines managed to spread the connection load on ISP gateway used in a balanced way. Size of the packets that are passed to each ISP is not balanced, because the PCC method only divides based on the connection, not the size of packets that pass through ISP. When one line is disconnected, internet connection will be automatically transferred to an active internet line.